Ethical considerations for involving adolescents in biomedical HIV prevention research - Nakalega, Rita; Akello, Carolyne; Gati, Brenda; Nakabiito, Clemensia; Nolan, Monica; Kamira, Betty; Etima, Juliane; Nakyanzi, Teopista; Kemigisha, Doreen; Nanziri, Sophie C.; Nanyonga, Stella; Nambusi, Maria Janine; et al. (BMC Medical Ethics, 2021)
Background: Involvement of adolescent girls in biomedical HIV research is essential to better understand efficacy and safety of new prevention interventions in this key population at high risk of HIV infection. However, there are many ethical issues to consider prior to engaging them in pivotal biomedical research. In Uganda, 16–17-year-old adolescents can access sexual and reproductive health services including for HIV or other sexually transmitted infections, contraception, and antenatal care without parental consent. In contrast, participation in HIV prevention research involving investigational new drugs requires adolescents to have parental or guardian consent. Thus, privacy and confidentiality concerns may deter adolescent participation. We describe community perspectives on ethical considerations for involving adolescent girls in the MTN 034 study in Uganda. Methods: From August 2017 to March 2018, we held five stakeholder engagement meetings in preparation for the MTN 034 study in Kampala, Uganda (NCT03593655): two with 140 community representatives, two with 125 adolescents, and one with 50 adolescents and parents. Discussions were moderated by the study team. Proceedings were documented by notetakers. Summary notes described community perspectives of adolescent participation in HIV research including convergent, divergent or minority views, challenges, and proposed solutions. Results: Most community members perceived parental or guardian consent as a principal barrier to study participation due to concerns about adolescent disclosure of pre-marital sex, which is a cultural taboo. Of 125 adolescent participants, 119 (95%) feared inadvertent disclosure of sexual activity to their parents. Community stakeholders identified the following critical considerations for ethical involvement of adolescents in HIV biomedical research: (1) involving key stakeholders in recruitment, (2) ensuring confidentiality of sensitive information about adolescent sexual activity, (3) informing adolescents about information to be disclosed to parents or guardians, (4) offering youth friendly services by appropriately trained staff, and (5) partnering with community youth organizations to maximize recruitment and retention. Conclusions: Stakeholder engagement with diverse community representatives prior to conducting adolescent HIV prevention research is critical to collectively shaping the research agenda, successfully recruiting and retaining
Keywords: Ethics; Adolescent girls; Biomedical HIV prevention research; Stakeholder engagement; Uganda